2020
DOI: 10.1021/acs.jpcb.0c00916
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dissociation Mechanism of Single-Walled Carbon Nanotube on Mature Amyloid-β Fibrils at Single Nanotube Level

Abstract: Amyloid fibrils originating from the fibrillogenesis of misfolded amyloid proteins are associated with the pathogenesis of many neurodegenerative diseases, such as Alzheimer's, Parkinson's, and Huntington's diseases. Carbon nanotubes have been extensively applied in our life and industry due to their unique chemical and physical properties. Nonetheless, the details between carbon nanotubes and mature amyloid fibrils remain elusive. In this study, we explored the interplay between single-walled carbon nanotubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 58 publications
3
49
0
Order By: Relevance
“…Shorter cross-over distances are also observed, but evolved with time, increasing from ∼40 nm at day 1 to ∼60 nm at day 7 and ∼70 nm at day 10 of incubation ( Figures 3H-J). At day 7 of incubation, twisted fibers are co-existing with non-twisted ones, though the later are a minority in our samples ( Figures 3A,B), and curved fibers are also present at day 10 in a low proportion ( Figure 3C), which is consistent with previously observed mature Aβ 1-42 WT fibers (Lin et al, 2020).…”
Section: L34t Amyloid Polymorphismsupporting
confidence: 92%
“…Shorter cross-over distances are also observed, but evolved with time, increasing from ∼40 nm at day 1 to ∼60 nm at day 7 and ∼70 nm at day 10 of incubation ( Figures 3H-J). At day 7 of incubation, twisted fibers are co-existing with non-twisted ones, though the later are a minority in our samples ( Figures 3A,B), and curved fibers are also present at day 10 in a low proportion ( Figure 3C), which is consistent with previously observed mature Aβ 1-42 WT fibers (Lin et al, 2020).…”
Section: L34t Amyloid Polymorphismsupporting
confidence: 92%
“…22 Lin et al investigated the dissociation mechanism between single-walled CNTs and mature amyloid fibers by experiments and molecular dynamics (MD) simulations. 23 Generally, there are many factors such as size, 24 shapes, 25 curvature, 26–28 effective hydrophobicity, 29 surface functionality, 30 and solubility 31 that affect the interactions between CNTs and proteins. In 2019, Zhang et al demonstrated that the structure of the Aβ 42 peptides can be significantly tuned by changing the curvature of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Second, although two different proteins and two fullerenes have been used, the DC 50 values were found to be quite similar, thus suggesting a common mechanism of fibrils disassembly regardless of fibrils formed by different proteins. Moreover, the DC 50 values obtained for studied fullerenes are lower in comparison with the DC 50 values reported previously for other types of nanosized materials, such as superparamagnetic iron oxide nanoparticles and cerium dioxide nanoparticles, and were calculated for insulin, lysozyme, alpha-lactalbumin, beta-lactoglobulin, Aβ-peptide, and others. High potential to disassemble amyloid fibrils was reported also for gold and silver nanoparticles/nanorods, especially with coapplication of radiation. Similar disassembly ability comparing to our study was observed for graphene oxide and carbon nanotubes. , It is important that low concentrations of NMP have very little impact on protein amyloid aggregates. The increasing NMP concentration up to 120 mg/mL (fullerene to protein (w/w) ratio 2:1) results in ∼20% decrease of ThT fluorescence, suggesting possible interaction of NMP with amyloid fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…62−65 Similar disassembly ability comparing to our study was observed for graphene oxide and carbon nanotubes. 66,67 It is important that low concentrations of NMP have very little impact on protein amyloid aggregates. The increasing NMP concentration up to 120 mg/mL (fullerene to protein (w/w) ratio 2:1) results in ∼20% decrease of ThT fluorescence, suggesting possible interaction of NMP with amyloid fibrils.…”
Section: Resultsmentioning
confidence: 99%